2019
DOI: 10.1007/s11678-019-0531-3
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic superior capsular reconstruction using a human dermal allograft in patients with and without preoperative pseudoparalysis

Abstract: Background Massive irreparable rotator cuff tears (RCT) may cause severe functional impairment and pain as a result of loss of superior humeral stability. Reconstruction of the superior capsule (SCR) has been reported to restore glenohumeral stability and function. Objective The purpose of this study was to investigate short-term functional and radiological outcome after arthroscopic SCR with a human dermal allograft for irreparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This proportion is among the lowest in the range of reported graft tears across different studies of ASCR and is lower than the reported proportion of graft tears among most of the studies of ASCR that used an HDA. 10,14 In the current study, the statistically significant interrater reliability for the Goutallier classification of the supraspinatus muscle was within the range of reliability statistics reported in other settings, such as those reported for preoperative MRI of supraspinatus tendon tears. 30,44 In the study by Lippe et al, 30 the interrater reliability for the Goutallier classification was fair to moderate (kappa = 0.41) and improved to moderate (kappa = 0.53) when using the dichotomized Goutallier classification of the supraspinatus.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This proportion is among the lowest in the range of reported graft tears across different studies of ASCR and is lower than the reported proportion of graft tears among most of the studies of ASCR that used an HDA. 10,14 In the current study, the statistically significant interrater reliability for the Goutallier classification of the supraspinatus muscle was within the range of reliability statistics reported in other settings, such as those reported for preoperative MRI of supraspinatus tendon tears. 30,44 In the study by Lippe et al, 30 the interrater reliability for the Goutallier classification was fair to moderate (kappa = 0.41) and improved to moderate (kappa = 0.53) when using the dichotomized Goutallier classification of the supraspinatus.…”
Section: Discussionsupporting
confidence: 81%
“…The preliminary clinical studies on ASCR using an HDA or LHBT autograft 6,12,41 did not reproduce the outcomes reported in the studies by Mihata et al 34,37 Survivorship of the graft was one of the differences in the reported outcomes. Clinical studies on ASCR using an HDA have reported a higher proportion of graft tears, ranging from 20% to 75% in the short term (minimum of 6-month to 2-year follow-up), 10,12,14,24,28,41,50 whereas studies using an FLA have reported proportions of graft tears ranging from 4.2% to 32% in the short to medium term (minimum of 6-month to 5-year follow-up). 10,11,28,29,34,36,37 It remains unclear and controversial whether the type of graft or type of graft construct used in ASCR is an important (or even the most important) factor in the clinical success of ASCR.…”
mentioning
confidence: 99%
“…Eight of these 9 studies reported a revision rate of 4% or less. ** In contrast, of the 16 clinical studies of ASCR that used allografts or xenografts published to date that reported a minimum follow-up of 6 months to 2 years, †† only 4 studies 13 , 29 , 41 , 50 reported an MRI evaluation of graft integrity for each of the enrolled patients, and the calculated graft tear proportion ranged from 18.5% to 50% in the first 6 to 12 months of follow-up. In the remaining 12 studies of ASCR that used allografts or xenografts, a selected subgroup of patients underwent MRI evaluation, resulting in a proportion that reflects only this selected subgroup’s graft tear rate.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure has previously been described in detail. 16 , 30 , 40 All surgical procedures were performed with patients in the beach-chair position under general anesthesia and interscalene plexus blockade. DB of the tear margins, comprehensive bursectomy, subacromial decompression, opening of the rotator interval, and tenotomy of the long head of the biceps tendon (LHBT) were performed in all patients.…”
Section: Methodsmentioning
confidence: 99%
“… 3 6 Alternatively, Hirarara et al 30 , 31 proposed the use of an acellular dermal allograft for SCR. 16 A recently published systematic review reported good to excellent clinical outcomes in patients with irreparable RC tears undergoing SCR using a fascia lata autograft or a dermal allograft at mean short-term follow-up of 15 to 48 months. 2 Moreover, return to sport after SCR was reported in up to 100% of the cohort on the competitive and recreational levels.…”
mentioning
confidence: 99%